Changes in disability in older adults with generalized radiographic osteoarthritis: A complex relationship with physical activity. (10th April 2017) - Tak, E.C.P.M.; van Meurs, J.B.; Bierma‐Zeinstra, S.M.A.; Hofman, A.; Hopman‐Rock, M.
Abstract: Objective: The aim of the present study was to report on factors associated with changes in disability after 5 years, with a focus on physical activity (PA) in community‐dwelling older adults with generalized radiographic osteoarthritis (GROA). Methods: Assessment of GROA (hand, knee, hip) and disability (Health Assessment Questionnaire) in the Rotterdam Study (cohort RS‐1, N  = 7, 983; with GROA, n  = 821). A good outcome at follow‐up was defined as improved or mild disability, and a poor outcome as worsened or severe disability. Factors potentially associated with outcome were demographics, joint complaints, other chronic health problems or limitations (body mass index, number of chronic conditions, cognition), and level of different types of PA. Some of these assessments were repeated in between 1997 and 1999 (RS‐3), and between 2002 and 2004 (RS‐4). Results: A total of 309 older adults with GROA and valid measures on RS‐3 and RS‐4 showed mild to moderate disability, with minor increases over 5 years (follow‐up N  = 287 RS‐3 to RS‐4). PA levels decreased with increasing disability, especially in sport and walking. PA was univariately associated with a better outcome at follow‐up but when adjusted for other factors (higher age, having knee pain and stiffness, and having more than two other chronic conditions) was associated with negative changes in general and lower limb disability, although not with upper limb disability. Conclusions: This was the first study to report that community‐dwelling older adults with GROA show moderate levels of disability, and that reduced levels of disability are associated with higher levels of PA, but when adjusted for other confounders this association is lost. Further research is needed to study the complex relationships between PA and other determinants of disability.